Estuaries as carbon sinks: photosynthetic activity, photoinhibition and resilience in pelagic-benthic primary production - Frankenbach, Silja (2020)
Estuaries are recognized amongst the most productive ecosystems on Earth. Their high primary productivity is largely due to the photosynthetic carbon fixation by phytoplankton and microphytobenthos, the communities of microalgae and cyanobacteria that inhabit the water column and subtidal or intertidal sediments, respectively. In comparison with the phytoplankton, the microphytobenthos has been much less studied regarding the photophysiological processes affecting primary productivity, and their relative role as contributors to estuarine-level production. One of these processes is photoinhibition, the high light-induced decrease in photosynthetic activity, considered a major limiting factor of growth and primary productivity in the variable and extreme estuarine environment. The detrimental impact of photoinhibition on photosynthesis depends on the balance between the photoinactivation and repair of photosystem II (PSII). By successfully adapting to microphytobenthos a recently-developed methodology based on multi-actinic imaging of chlorophyll fluorescence, this work evaluated their photoacclimation and photoprotective capacity, as measured by the reduction in PSII photoinactivation. PSII photoinactivation and repair was found to vary between different communities, pointing to a trade-off between cellular motility-based and physiological photoprotective mechanisms. Epipelic (motile) species showed a reduced physiological capacity for preventing photodamage, while epipsammic (non-motile) forms appeared less susceptible to photoinactivation and more dependent on physiological photoprotection. This work further investigated an overlooked aspect of microphytobenthos ecology, related to the presence of substantial amounts of microalgal biomass in subsurface sediments. By studying samples from intertidal areas of the Ria de Aveiro (Portugal), this work found that buried cells can quickly regain photosynthetic activity when exposed to surface conditions. Potential viable subsurface (0.5-10 cm) microalgal biomass was found to represent 2-3 times the amount of biomass present at the surface layers (0.0-0.5 cm). These results support the hypothesis that subsurface biomass may play an important ecological role as a source of photosynthetically competent cells capable of ‘reinoculating’ the surface, contributing to the high productivity of intertidal areas. The relative importance of phytoplankton and microphytobenthos as contributors to ecosystem-level primary productivity was evaluated in the Ria de Aveiro, by comparing the spatio-temporal variability of biomass and productivity of different communities. This study made use of a new type of fluorometer allowing the measurement of absolute rates of PSII electron transport rates and the estimation of carbon fixation rates. Biomass-specific productivity rates for phytoplankton and microphytobenthos were found to reach 68.0 and 19.1 mg C mg Chl a-1 d-1, respectively. Annual areal production rates were higher for the microphytobenthos, reaching 105.2 g C m-2 yr-1, as opposed to 49.9 g C m-2 yr-1 for the phytoplankton. The annual rates upscaled for the whole Ria de Aveiro highlight the importance of the intertidal areas as significant carbon sinks and reservoirs of active ‘blue carbon’, and as main sites of primary productivity, found to contribute with more than 60% of the total ecosystem-level budget 12428.3 t C yr-1.